Integration of Action and Size Perception Through Practice. (October 2017) - Coutte, Alexandre; Camus, Thomas; Heurley, Loïc; Brouillet, Denis
Size perception is known to influence our usual interactions with environment. Numerous studies highlighted that during the visual presentation of an object, the properties of manual actions vary as a function of this object's size. In order to better understand the dynamic variations of relationships between size perception and action, we used an experimental paradigm consisting in two phases. During a previous implicit learning phase, a manual response (right or left) was specifically associated with the appearance of a large or small stimulus. During further test phase, participants were required to prepare a response while discriminating the color of a stimulus (GO/No GO task). We observed that the response execution was faster when the size of the stimulus was congruent with the size that had been associated to this response (during implicit learning phase). These results suggest that when a response usually co-occurs with visual stimuli characterized by a specific size pattern, the response and the size pattern become integrated. Any subsequent preparation and execution of this action are therefore influenced by the reactivation of this visual pattern. This result brings out new insights on how sensorimotor interactions may modulate the ability to anticipate perceptive size variations in the environment.